2012
DOI: 10.1210/jc.2011-3136
|View full text |Cite
|
Sign up to set email alerts
|

Hypermethylated in Cancer 1 (HIC1), a Tumor Suppressor Gene Epigenetically Deregulated in Hyperparathyroid Tumors by Histone H3 Lysine Modification

Abstract: The results strongly support a growth-regulatory role of HIC1 in the parathyroid glands and suggest that perturbed expression of HIC1 may represent an early event during tumor development. Repressive histone modification H3K27me2/3 is involved in repression of HIC1 expression in hyperparathyroid tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 31 publications
3
35
0
Order By: Relevance
“…To our knowledge, EZH2 gene amplification presents the first genetic aberration common to a subset of parathyroid adenomas, secondary hyperplastic parathyroid glands, and parathyroid carcinomas. This further supports the possibility of a common pathway in parathyroid tumor development (Svedlund et al 2012). Interestingly, somatic EZH2 Y641N mutations were recently observed in parathyroid adenomas (Cromer et al 2012), albeit at a very low frequency (two out of 193).…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…To our knowledge, EZH2 gene amplification presents the first genetic aberration common to a subset of parathyroid adenomas, secondary hyperplastic parathyroid glands, and parathyroid carcinomas. This further supports the possibility of a common pathway in parathyroid tumor development (Svedlund et al 2012). Interestingly, somatic EZH2 Y641N mutations were recently observed in parathyroid adenomas (Cromer et al 2012), albeit at a very low frequency (two out of 193).…”
Section: Discussionsupporting
confidence: 76%
“…The cells were harvested after 120 h and RNA/protein was extracted. The cells were transfected for 48 h and then transfected again and further incubated for 72 h (Svedlund et al 2012). …”
Section: Cell Culture and Transfectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Promoter hypermethylation of the tumor suppressor gene, hypermethylated in cancer 1 (HIC1), has been shown to be frequently repressed in parathyroid cancer (Svedlund et al 2012). A growth-regulatory role has been assigned to HIC1 in the parathyroid glands and it is suggested that its downmodulation might be an early event in tumoral transformation, where, in addition to DNA methylation, other epigenetic mechanisms such as repressive histone marks (H3K27me2/3) play a part (Table 1).…”
Section: Sporadic Endocrine Diseasesmentioning
confidence: 99%